The Green Revolution revisited : critique and alternatives - Glaeser, Bernhard (Routledge library editions. Development ;, 2011)
The Green Revolution - the apparently miraculous increase in cereal crop yields achieved in the 1960s - came under severe criticism in the 1970s because of its demands for optimal irrigation, intensive use of fertilisers and pesticides; its damaging impact on social structures; and its monoculture approach. The early 1980s saw a concerted approach to many of these criticisms under the auspices of Consultative Group on International Agricultural Research (CGIAR). This book, first published in 1987, analyses the recent achievements of the CGIAR and examines the Green Revolution concept in South.